Are public policies effective in alleviating family income inequality in Iran? - Khiabani, Nasser; Mazyaki, Ali (Journal of Income Distribution®, 2009)
Redistributing incomes has always been one of the main goals of Iranian policy makers, although political regimes have changed frequently between 1991 and 2004. We have applied a microsimulation using the Oaxaca-Blinder decomposition and a Heckman correction for sample selection bias to compare simulation results for a hypothetical unchanged situation with the actual policy shift observed. While we are able to identify the years in which policy shifts occurred, our results suggest that the intended redistribution goals were at most partially achieved, affecting only some occupations and being offset by changes to the level of family incomes.